Exploration of Antibacterial Compounds From Bacillus velezensis BP1 Against Foodborne Pathogens Staphylococcus aureus and Salmonella enterica Typhimurium Using Metabolomic and Genomic Approaches - Tsania Taskia Nabila; Ema Damayanti; Jaka Widada (Journal of Food Protection)
Food contamination by pathogenic microorganisms has become a significant issue. This study investigated the antibacterial compounds of a Bacillus isolate from stingless bee bread, Bacillus velezensis BP1, against foodborne pathogens Staphylococcus aureus ATCC 25923 and Salmonella enterica Typhimurium ATCC 14028 using the one strain many compounds (OSMAC), metabolomic, and genomic approaches. The culture media used were Tryptic Soy Broth (TSB), TSB with Chitosan (TSB-Chi), several synthetic broths composed of Mineral Salts with Glucose (MG) and Glucose-Fructose (MGF), Carboxymethyl Cellulose (CMC), and Starch Nitrate (SNB), to analyze diverse antibacterial compounds. Twelve extracts from the supernatant (S) and pellet (P) were screened using the microdilution method. P-TSB and S-TSB-Chi demonstrated the highest antibacterial effects, with inhibitory concentration (IC50) values of 253.5 ppm and 740.28 ppm, respectively. Fourier transform infrared spectroscopy (FTIR) analysis identified an amide I group contributing to extract clustering. Untargeted liquid chromatography-high resolution mass spectrometry (LC-HRMS) revealed six compounds significantly contributing to extract clustering. Enrichment analysis showed that chitosan was associated with the metabolic processes of pyrimidine and nucleotide metabolisms. Growth curve assay and scanning electron microscopy (SEM) confirmed the extracts’ efficacy. The Bacillus isolate showed an average nucleotide identity (ANI) of 98.08% to Bacillus velezensis NRRL B-41580. Genome mining revealed twelve biosynthetic gene clusters, six 100% similar to known clusters. Molecular docking demonstrated that genome mining-derived bacillibactin and LC-HRMS-derived bis(4-ethylbenzylidene)sorbitol and cyclo(phenylalanyl-prolyl) exhibited the strongest binding affinities against four pathogen-associated proteins, outperforming ampicillin. This study highlights Bacillus velezensis BP1’s potential as a source of diverse antibacterial compounds.